Contributions to Nephrology 2006
DOI: 10.1159/000096764
|View full text |Cite
|
Sign up to set email alerts
|

The Mesangium as a Target for Glomerulopathic Light and Heavy Chains: Pathogenic Considerations in Light and Heavy Chain-Mediated Glomerular Damage

Abstract: Certain structurally abnormal light and heavy chains are known to be nephrotoxic and alter mesangial homeostasis producing pathological alterations. Many of the mechanisms involved in light chain-mesangial interactions have been deciphered using an in vitro model, providing a framework for understanding the sequence of events that leads to irreversible glomerular changes and eventually renal failure. The molecular events involved in the pathogenesis of these disorders are now for the most part well-established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
0
22
0
1
Order By: Relevance
“…Recent studies demonstrated that monoclonal FLC promote proximal tubular injury by increasing intracellular oxidative stress with the subsequent production of monocyte chemoattractant protein 1 (28). Further work has shown that FLC induce epithelial-mesangial transition (29) and activate mesangial cells to proliferate and increase production of matrix proteins (30). The hypothesis that polyclonal FLC present in increasing concentrations in patients with CKD may be capable of inducing similar injuries is now being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that monoclonal FLC promote proximal tubular injury by increasing intracellular oxidative stress with the subsequent production of monocyte chemoattractant protein 1 (28). Further work has shown that FLC induce epithelial-mesangial transition (29) and activate mesangial cells to proliferate and increase production of matrix proteins (30). The hypothesis that polyclonal FLC present in increasing concentrations in patients with CKD may be capable of inducing similar injuries is now being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 These proinflammatory cytokines promote infiltration by inflammatory cells that produce metalloproteinases and increase transforming growth factor-b production, resulting in matrix protein deposition and subsequent fibrosis and further compromising the ability of the nephron to restore function. 25 Light chains endocytosis may also cause tubular cell necrosis, leading to more severe renal dysfunction. 26 The exact mechanism has not been clarified, but it has been suggested that aggregation of light chains after endocytosis may initiate a cascade resulting in tubular cell death.…”
Section: Pathogenesismentioning
confidence: 99%
“…Our findings establish that a lower percentage of urine k FLC excretion associates with higher proteinuria, lower levels of eGFR, and higher histologic score in patients with IgAN. The design of the present study does not allow us to propose a mechanism responsible for the glomerular capture of k FLC or establish a role of k FLC renal deposition in the onset and progression of renal damage of IgAN, but the available literature suggests several possibilities, whereby k FLC deposition could promote renal injury (39,40).…”
Section: Discussionmentioning
confidence: 88%